(untitled) (Journal on studies and research of academic knowledge, 2008)
We sought to develop an Environmental Assessment Municipal City incarnation, considering the criteria set out in Agenda 21. The study was descriptive and quantitative and qualitative tools were conducted surveys of public opinion poll in 29 districts of the municipality and interviews with municipal authorities related to the environment. The results showed that the public feels dissatisfied and improve aspects such as: 81% public transportation, public safety 52%, 48% refuse collection, among others. For the most part expressed the need to increase green space for public use due to urban growth and high propensity to classify waste. Those responsible. for the improvement are: the municipality (99%), the Government Departmental (81%), citizens (59%), neighborhood committees (51%) and others. The highlighted environmental awareness, lack of citizen participation in community projects and willingness to adopt better environmental practices betting on environmental education as a priority of the municipality.